Legality In Hospitals- Medico-Legal Case Management (Medico Legal Update, 2020)
The growing number of legal issues in various fields and specialties in the current era has been no differentin the healthcare sector. The complexity associated with such issues has been the major concern of practicingdoctors/healthcare professionals. In this article, an attempt has been made to focus the legalities in the fieldof medicine with an emphasis on the Indian set up and existing Laws governing such actions. The articlecomprises of medico-legal case management, awareness and prevalent practices among the health careprofessionals especially among those who are directly or indirectly involved with the treatment of patients.As far the awareness is concerned regarding a procedure, the documentation and various other medico-legalissues were studied in detail. Also, various aspects of medico-legal cases admitted in the hospital.